Pengaruh Literasi Pasar Modal Terhadap Keputusan Investasi Saham Mahasiswa Politeknik PIKSI Ganesha Bandung - Gunardi Gunardi; Syamsu Yusuf; Perwito Perwito; Adri Arisena (IKOPIN, 2020)
Understanding and capital market literacy is needed in determining investment decisions. Likewise with an understanding of capital market products needed by students or young people to invest. One that helps students determine investment decisions is to provide capital market literacy in the form of workshops, seminars, Capital Market Schools (CMS). This is an activity that students must follow to determine the best investment decisions and which in turn will improve Indonesia's economic development through the existence of the investment. The sample of this study was 98 people drawn from the population of the Piksi Ganesha Polytechnic Investment Gallery Investor. This research is a quantitative study, aimed to find out how much influence the capital market literacy has on the decision to invest in student shares in Piksi Ganesha Polytechnic.